Agile Software Development - Bhatti, Simran; Tayal, Vandana; Gulia, Pooja (IJRDO -Journal of Computer Science Engineering, 2015)
In software application development, agile software development (ASD) is a methodology for the creative process that predicts the need for flexibility and applies a level of soberness into the delivery of the finished product. It is about how to work together to achieve a common goal. This paper focuses on how technology team, work together to plan, build and deliver software. It is a group of software development methods in which requirements and solutions grow through fraternization between self-organizing, cross-functional teams.